Four-wave mixing crosstalk suppression based on the pairing combinations of differently linear-polarized optical signals - Abd H.; Din N.M.; Al-Mansoori M.H.; Abdullah F.; Fadhil H.A. (The Scientific World Journal, 2023)
A new approach to suppressing the four-wave mixing (FWM) crosstalk by using the pairing combinations of differently linear-polarized optical signals was investigated. The simulation was conducted using a four-channel system, and the total data rate was 40 Gb/s. A comparative study on the suppression of FWM for existing and suggested techniques was conducted by varying the input power from 2 dBm to 14 dBm. The robustness of the proposed technique was examined with two types of optical fiber, namely, single-mode fiber (SMF) and dispersion-shifted fiber (DSF). The FWM power drastically reduced to less than -68 and -25 dBm at an input power of 14 dBm, when the polarization technique was conducted for SMF and DSF, respectively. With the conventional method, the FWM powers were, respectively, -56 and -20 dBm. The system performance greatly improved with the proposed polarization approach, where the bit error rates (BERs) at the first channel were 2.57 × 10 - 40 and 3.47 × 10 - 29 at received powers of -4.90 and -13.84 dBm for SMF and DSF, respectively. © 2014 Haider Abd et al.